Phase 2 randomized placebo controlled double blind study to assess the efficacy and safety of tecfidera in patients with amyotrophic lateral sclerosis (TEALS Study): Study protocol clinical trial (SPIRIT Compliant) - Vucic, Steve (Medicine (Baltimore), 2020)
BACKGROUND: Amyotrophic lateral sclerosis (ALS) is a progressive and fatal neurodegenerative disorder of the human motor system. Neuroinflammation appears to be an important modulator of disease progression in ALS. Specifically, reduction of regulatory T cell (Treg) levels, along with an increase in pro-inflammatory effector T cells, macrophage activation and upregulation of co-stimulatory pathways have all been associated with a rapid disease course in ALS. Autologous infusion of expanded Tregs into sporadic ALS patients, resulted in greater suppressive function, slowing of disease progression and stabilization of respiratory function. Tecfidera (dimethyl fumarate) increases the ratio of anti-inflammatory (Treg) to proinflammatory T-cells in patients with relapsing remitting multiple sclerosis and rebalances the regulatory: inflammatory axis towards a neuroprotective phenotype. Consequently, the aim of this study was to assess the efficacy, safety, and tolerability of Tecfidera in sporadic ALS. METHODS: The study is an investigator led Phase 2 multi-center, randomized, placebo controlled, double blind clinical trial assessing the efficacy and safety of Tecfidera in patients with sporadic ALS. The study duration is 40 weeks, with a 36-week study period and end of study visit occurring at 40 weeks or at early termination/withdrawal from study. The TEALS study has been registered with the Australian and New Zealand Clinical Trials registry (ANZCTR) under the trials registration number ACTRN12618000534280 and has been approved by the Human Research Ethics Committee and Research Governance Office at the lead site (Westmead Hospital) with the ethics number HREC/17/WMEAD/353. The participating sites have obtained site specific ethics and governance approvals from the local institution. RESULTS: The primary endpoint is slowing of disease progression as reflected by the differences in the ALS Functional Rating Score-Revised (ALSFRS-R) score at Week 36. The secondary endpoints will include effects in survival, lower motor neuron function, respiratory function, quality of life and safety. CONCLUSION: This Phase 2 multi-center, randomized, placebo controlled, double blind clinical trial will provide evidence of efficacy and safety of Tecfidera in sporadic ALS.